Improved diagnosis of tuberculous pleural effusion by combining medical thoracoscopy with Interferon-Gamma Release Assay and adenosine deaminase activity - FU,Zhihui (2022)
Abstract Rapid, accurate, affordable, point-of-care tuberculosis (TB) diagnostic tests are essential for controlling TB. We aimed evaluate the diagnostic performance of tuberculous pleural effusion by combining medical thoracoscopy with blood interferon-gamma release assay (IGRA) and pleural fluid adenosine deaminase (ADA). Patients with undiagnosed pleural effusion measured by chest X-ray or ultrasound were prospectively enrolled in this study. Medical thoracoscopy, blood IGRA and pleural fluid ADA were conducted.A total of 154 patients with undiagnosed pleural effusion were enrolled. Among them, 98 patients (63.6%) were diagnosed as TPE. Patients in TPE+ groups were significantly younger. The diagnostic thresholds obtained via receiver operating characteristic curve analysis were: ADA 23.4 U/L with AUC 0.91 (95% CI: 0.85-0.97, Figure 2) and IFN-γ 6.9 pg/mL with AUC 0.87 (95% CI: 0.82-0.93). By combining all three test together, we achieved sensitivity of 0.92, perfect specificity and NLR of 0.082. The AUC of the combination test was 0.96 (0.93-0.99), which was significant higher than any individual test (p < 0.001). The combination of medical thoracoscopy with Interferon-Gamma release assay and adenosine deaminase performs better than individual test in diagnosis TPE. The combination diagnosis has very high diagnostic rate, can be easily and safely carried out.